Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Pengungkapan CSR - Putri, Rafika Anggraini (Business Accounting Review, 2014)
This study aimed to find out the affect of variables such profitability, liquidity, and leverage to Corporate Social Responsibility (CSR) Disclosure. Type of this research used was quantitative research. The total companies used in this research were 19 companies which got ISRA award and public companies that listed in Bursa Efek Indonesia (BEI) period 2010-2012. This research used multiple regression analysis. The result showed that profitability and leverageÂ had no affect on CSR Disclosure, while liquidity had an affect on CSR Disclosure.